Can the Sustainable Development Goals (SDGs) be achieved by 2030? / Dr. Muhammad Zarunnaim Wahab and Dr. Mohamad Hanif Abu Hassan - Wahab, Muhammad Zarunnaim; Abu Hassan, Mohamad Hanif (Universiti Teknologi MARA, Kedah, 2024)
The Sustainable Development Goals (SDGs) represent a visionary concept with the ambitious objective of being achieved by the year 2030. As the global community stands with less than six years remaining to realize these goals, scholars are increasingly engaging in debates surrounding the feasibility of reaching these targets within the stipulated timeframe (Shulla & Leal Filho, 2023; Moyer and Hedden, 2020; Leal Filho et al., 2020; Hoy, 2015). Consequently, this article endeavors to provide a comprehensive overview by capturing insights from various studies and reports, drawing upon existing literature reviews to shed light on the current discourse surrounding the achievement of the SDGs. Upon conducting a comprehensive analysis of the literature, it becomes evident that a predominant focus among scholars is on various impediments that could hinder the realization of the SDGs. The primary concerns highlighted include the global pandemic, geopolitical conflicts, economic uncertainty, resource constraints, and political instability. These factors collectively underscore the intricate challenges that must be addressed to navigate the path toward achieving sustainable development on a global scale.